2021
DOI: 10.3390/en14217363
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of a Thermally Activated Ceiling Containing Phase Change Material for Different Cooling Load Profiles

Abstract: Increasing peak power demand implies the increasing significance of energy storage. Technologies that efficiently store heat and cold are also important for increasing the share of renewables and improving the efficiency of heating, ventilation, and air conditioning (HVAC) systems. The present experimental study investigated the dynamic behavior of a room with suspended thermally activated ceiling panels filled with a material containing 60% paraffin. The purpose of the study was to determine the specific cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The filling of the PCM with thermally activated ceilings ensured stabilization of the indoor air temperature and improved thermal comfort. However, the air temperature of the room is sensitive to the activation of pump circulation and the thermal conduction of the ceiling panel filling 65 . In extremely cold climates such as China, a simulation study has demonstrated that the application of TABS‐PCM in the northern orientation increases the indoor air temperature by 1.8°C, thus reducing the thermal discomfort of the building 66 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filling of the PCM with thermally activated ceilings ensured stabilization of the indoor air temperature and improved thermal comfort. However, the air temperature of the room is sensitive to the activation of pump circulation and the thermal conduction of the ceiling panel filling 65 . In extremely cold climates such as China, a simulation study has demonstrated that the application of TABS‐PCM in the northern orientation increases the indoor air temperature by 1.8°C, thus reducing the thermal discomfort of the building 66 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the air temperature of the room is sensitive to the activation of pump circulation and the thermal conduction of the ceiling panel filling. 65 In extremely cold climates such as China, a simulation study has demonstrated that the application of TABS-PCM in the northern orientation increases the indoor air temperature by 1.8 C, thus reducing the thermal discomfort of the building. 66 The current literature review has shown that there are limited comprehensive indoor thermal studies on TABS-PCMs under different climates.…”
Section: Effect Of Pcms In Thermally Activated Building Systemsmentioning
confidence: 99%
“…The linear fitting (red line) is quite straightforward, as can be anticipated -humans work and learn better when they are satisfied with their indoor environment. Despite a large number of factors influencing human sensations and perceptions, thermal environment and heat transfer issues might be considered as a dominant force [15][16][17][18][19][20][21]. However, an important element is also noise [22] and future studies might be focused on this aspect due to its possible impact on the general sensations and productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Sinacka and Szczechowiak [56] studied the dynamic behaviour of a room with hanging thermally triggered ceiling panels packed with 60% paraffin. The densities of convective and radiant heat fluxes, as well as the coefficients of heat transfer at the ceiling surface, Bogatu et al [54] evaluated a new macro-encapsulated PCM panel (MEP) with integrated pipes compared to commercial radiant cooling technologies as an effective ceiling cooling component.…”
Section: Studies Related To Pcms In the Ceilings Of Residual Buildingsmentioning
confidence: 99%
“…Sinacka and Szczechowiak [56] studied the dynamic behaviour of a room with hanging thermally triggered ceiling panels packed with 60% paraffin. The densities of convective and radiant heat fluxes, as well as the coefficients of heat transfer at the ceiling surface, were computed.…”
Section: Studies Related To Pcms In the Ceilings Of Residual Buildingsmentioning
confidence: 99%